Composting dead swine - Murphy, James P.; Harner, Joseph P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Composting dead animals from a swine production facility offers an environmentally sound disposal method to many producers
Keywords: Swine; Composting; Dead swine